Perspektif Transaksi E-Commerce di Era Globalisasi Perdagangan Bebas dalam Hukum Perjanjian di Indonesia - Alif, Rizal (UI Scholars Hub, 2008)
In the era of business globalization, market depends heavily in the Information Technology (IT) especially the internet which gives benefits of time efficiency to entrepreneurs. In Indonesia, however, there is no legal certainty in this matter due to pending bills in the legislative body (DPR). Further, there are many more problems related to e-commerce transactions which frequently crossing the state-borders, such as jurisdiction, choice of law and forum, validity of treaty and legal protection to the trader. This article tries to discuss and analyze those problems from the Indonesian law on agreement in order to anticipate the global business transactions through e-commerce.